2017
DOI: 10.1177/0363546517709780
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Tear Progression in Symptomatic Rotator Cuff Tears: A Prospective Study of 174 Shoulders

Abstract: The tear size of symptomatic rotator cuff tears progressed in 47% of the shoulders during a mean of 19 months, and the speed of progression was 3.8 mm/y in length and 2.0 mm/y in width. The risk factors for tear progression were (1) a medium-sized tear, (2) a full-thickness tear, and (3) smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
1
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 30 publications
2
66
1
4
Order By: Relevance
“…Although our results are in agreement with the hypothesis that the increased ratio of type I/III collagen may be indicative of the repair response, our clinical findings show that the ratio of type I/III collagen cannot be used as a single marker of total repair, as previously postulated . Our clinical observations indicate that the attempted intrinsic tendon repair is insufficient to reestablish tissue integrity, and surgical treatment is necessary, even in patients who have experienced a longer disease period (personal note), which agrees with Yamamoto et al study demonstrating clinically the absence of healing and progression of about 47% of the shoulders tears …”
Section: Discussionsupporting
confidence: 92%
“…Although our results are in agreement with the hypothesis that the increased ratio of type I/III collagen may be indicative of the repair response, our clinical findings show that the ratio of type I/III collagen cannot be used as a single marker of total repair, as previously postulated . Our clinical observations indicate that the attempted intrinsic tendon repair is insufficient to reestablish tissue integrity, and surgical treatment is necessary, even in patients who have experienced a longer disease period (personal note), which agrees with Yamamoto et al study demonstrating clinically the absence of healing and progression of about 47% of the shoulders tears …”
Section: Discussionsupporting
confidence: 92%
“…Non‐surgical treatment of RCTs is effective in more than 70% of patients. However, it is important for surgeons to know the risk factors for tear progression because surgery should be performed at the appropriate time (especially in small‐ to medium‐sized tears) to obtain optimal clinical results . Therefore, knowledge of patient susceptibility may help in the determination of the best treatment options for each patient; for example, early surgery could be discussed with patients who are more likely to have a tear that progresses faster or have recurrent disease.…”
mentioning
confidence: 99%
“…In paper I, we identified age and having a fullthickness tear as significant factors in multivariable logistic regression. Both age 177 and full-thickness tear 141,177,265 , have been identified in other studies as well and additional factors identified include pain 175,199,241 , smoking 265 and dominant side 141 . It is likely, but not convincingly shown as of yet in prospective studies, that identifying known risk factors for rotator cuff tear may aid in identifying patients at risk for tear progression with non-operative treatment, but factors that are currently unknown or unreachable to clinicians (like genetic factors) may be of greater importance.…”
Section: Discussionmentioning
confidence: 66%
“…The rate of progression seem however to be slow and require several years in many patients, and, estimated from 8 studies on asymptomatic and symptomatic patients, has been suggested to be 0.91 % per month 157 . Another estimate of progression rate is 2 mm/year for width and 3.8 mm/year for length 265 . Most studies have been performed on patients with small tears however, and the progression rate may differ depending on tear size 204 .…”
Section: Discussionmentioning
confidence: 99%